(3QSGdI aj eSCdI GdcSHs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb cd TF abOQg JbOjQkG hHYO aEfc PcQJ Cf eSCdI GdcSH hJejjRg GdPi gh GdePgH GdMb Yf GdePgHjf GdaGSOjf hgeG ePgHG GdLHQjI hGdbOQjI eeG EdJHS Ydjc s
(3BNQgG (B:s
(3aOhfcgG QSGdI LeYJ dc ajgG eG jTai hjcai hGdMeO ddg QHfG BefkG HeG CfRdJ bGd eDda hcJH KGfi YTQ UaQ GdNjQ ef YGe (B1276 (3g` s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds